The Negro's Civil War how American Negroes felt and acted during the war for the Union - McPherson, James M. (New York Pantheon Books, 1965)
Uses excerpts from speeches, letters, articles, and official documents to point out the military and political contributions and the feelings of Afro-Americans during the Civil War.
"A note on sources": p. [343]-347.
Keywords: United States -- History -- Civil War -- Negroes